High-degree hydrolysis sea cucumber peptides improve exercise performance and exert antifatigue effect via activating the NRF2 and AMPK signaling pathways in mice. (November 2021) - Wang, Qianqian; Shi, Jinyuan; Zhong, Hao; Abdullah,; Zhuang, Jiachen; Zhang, Junhui; Wang, Jing; Zhang, Xi; Feng, Fengqin
Graphical abstract: Highlights: Two sea cucumber-derived peptides with different hydrolysis degree were identified. Both SCP-1 and SCP-2 improve exercise performance and delayed physical fatigue. The antifatigue activity of SCP-2 was stronger than that of SCP-1. SCP enhance antifatigue effect by regulating NRF2/ARE and AMPK/PGC-1α pathways. Abstract: In this study, the antifatigue potential of two sea cucumber peptides (SCP), with low hydrolysis degree (SCP-1) and high hydrolysis degree (SCP-2) derived from Acaudina leucoprocta was investigated. SCP-2 had a lower molecular weight, shorter peptide length, and higher proportion of identified sequences related to branched chain amino acids than SCP-1. Both SCP-1 and SCP-2 significantly improved exercise performance and exerted antifatigue effects in comparison to the negative control group (NC). The mice group received SCP-2 treatment showed better antifatigue effects than that of SCP-1 by prolonging exhaustive swimming time, increasing forelimb grip strength, reducing metabolite accumulation, relieving muscle injury, enhancing muscle glycogen and energy metabolism. Besides, these two treatments significantly modulated the protein relative levels of oxidative stress and mitochondrial function by regulating the NRF2 and AMPK signaling pathways. Conclusively, the study's findings suggested that SCP could possibly be used as a green functional ingredient to overcome fatigue.